Pengembangan Modul Ajar P5-PPRA pada Pembelajaran Matematika Madrasah Ibtidaiyah - Corah, Corah; Riawarda, Andi; Hisbullah, Hisbullah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The implementation of the Merdeka Curriculum in madrasah ibtidaiyah requires the availability of learning tools that not only support the achievement of academic competencies but also integrate character education through the Pancasila Student Profile Strengthening Project and the Rahmatan Lil’ Alamin Student Profile (P5-PPRA). However, many madrasahs still face limitations in providing contextual, systematic teaching modules that align with the characteristics of early-grade learners. This study aims to develop mathematics teaching modules on addition and subtraction for Grade I Madrasah Ibtidaiyah that integrate P5-PPRA values and to examine their validity and practicality. The study employed a Research and Development (R&D) approach, encompassing needs analysis, product Design, module development, and evaluation through expert validation and practicality testing. The research subjects were first-grade teachers and students at Madrasah Ibtidaiyah DDI Palopo, while subject-matter, linguistic, and instructional Design experts served as feasibility assessors. The results indicate that the developed module achieved high validity across all assessment aspects and demonstrated very high practicality, as indicated by teacher and student responses. These findings show that integrating P5-PPRA values into early mathematics instruction can be effectively implemented without reducing the clarity of numeracy concepts. This study contributes to strengthening integrative learning practices in madrasah ibtidaiyah and provides an initial reference for teachers in developing mathematics teaching modules aligned with the Merdeka Curriculum.